ASUHAN KEBIDANAN KOMPREHENSIF PADA NY L UMUR 36 TAHUN DI PUSKESMAS SAPURAN KABUPATEN WONOSOBO - Dewi Candra Resmi; Annisa Rahmawati; Indrawati Aris Tyarini; Prasetyaning Dwiworo (Jurnal Ilmiah Kesehatan, 2025)
Comprehensive Midwifery Care is a midwifery service that is provided comprehensively, continuously and consistently to a mother, starting from pregnancy to Family Planning services. The purpose of this study is to provide comprehensive midwifery care (Continuity of Care) using the SOAP method as an effort to reduce maternal mortality and infant mortality rates. The subject of this study was Mrs. L, 36 years old. The assessment was conducted from March 4 to April 13, 2025. During the pregnancy phase, it was found that Mrs. L was at high risk due to advanced maternal age (over 35 years) and obesity. Mother gives birth normally, baby is born healthy. During neonatal care, the baby was found to have complaint of poor breastfeeding. In the postpartum care, the mother have a complication of breast engorgement. Family planning care with no complications observed, mother usescontraceptive implant. A gap between theory and practice was found regarding the implementation of Early Initiation of Breastfeeding. Based on the assesment, it’s recommended to improve midwifery sevices continue, particulary in early detection and prevention of complications.